Transparansi Penerimaan Negara Bukan Pajak (PNBP) Pada Kepolisian Negara Republik Indonesia Menuju Good Police Governance - Arifin Ma’ruf (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2018)
The results showed that PNBP or Non-Tax State Revenue is one of the revenues ofthe State that comes from non-taxation. In the Police of the Republic of IndonesiaPNBP is regulated in Government Regulation No. 60 of 2016 on Types and Tariffsof Non-Tax State Revenues Applicable to the Police of the Republic of Indonesia. Theregulation is the latest regulation that replaces the previous regulation contained inGovernment Regulation No. 50 of 2010. The results of the analysis in this studyindicate that PNBP in the Police of the Republic of Indonesia must be reported to thepublic. This is in accordance with the provisions contained in Article 9 of LawNumber 14 Year 2008 on Transparency of Public Information that the financialstatements are one of the information that can be accessed by the public and must bereported periodically either through information board media or through electronicmedia. In order to realize Good Police Governance, financial transparency of PNBPbecomes very important.